CSR AND ACCOUNTING: SYNERGIES TO BUILD AN ETHICAL CORPORATE REPUTATION ERETIKA - Ika Ariyani; Ersi Sisdianto (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to explore the relationship between Corporate Social Responsibility (CSR) and accounting in the context of building an ethical corporate reputation. Using a qualitative approach through literature studies, this study analyzes a variety of relevant literature and previous studies to understand how CSR can be integrated into accounting practices. The results showed that good CSR practices contribute positively to the company's reputation, increasing consumer and investor confidence. In addition, the disclosure of CSR-related information in accounting reports is important to create transparency and accountability. The study found that companies that actively report on their CSR initiatives not only reinforce a positive image in the eyes of the public but can also reduce the risk of a negative reputation due to a crisis or scandal. Although there is a positive relationship between CSR and reputation, the direct impact on a company's financial performance still requires further research to understand the variables that mediate the relationship. This study concludes that the integration between CSR and accounting is very important to build a positive image of the company in the eyes of the public. Therefore, companies are advised to develop comprehensive CSR policies and conduct transparent disclosures on the social and environmental impacts of their activities. Thus, the study provides valuable insights for future business practices and supports sustainability goals.